ANALISIS PELAKSANAAN PUTUSAN PERADILAN AGAMA TERHADAP NAFKAH PERCERAIAN DALAM PRESPEKTIF HUKUM NASIONAL DAN HUKUM ISLAM BAGI PNS - Rendra Widyakso; Fifik Wiryani (Universitas Muhammadiyah Malang, 2021)
Decisions can be executed if, a court decision contains an order for one of the parties to pay a sum of money or vacate a permanent object. Usually, divorce cases that occur will punish the husband to make a payment of some money as a living for the divorced wife after the Religious Court Judge decides. The penalty is in the form of giving 1/3 (one third) of the salary given to the ex-wife and 1/3 (one third) of the others assigned to his child. Based on Government Regulation No. 10 of 1983 jo Government Regulation No. 45 of 1990, the penalty applies to husbands who work as Civil Servants (PNS). In some case adoption of decisions, often not going well even not implemented. Therefore, many respondents demanded the Petitioner to provide several divorce wages, such as mut' ah payments for livelihoods, iddah income, and Ahmadiyah livelihoods, which were carried out before the promise of divorce was pronounced and had to make a living. For sacrifice after the execution of the divorce agreement is canceled. The Panel of Judges will grant such a request, but this request is not for civil servants. So, the authors conducted research using the juridical-normative method to examine the source of law in the Regulations stated in the Religious Court decision. The results obtained that the panel of judges in their decision view that the regulation is only an administrative requirement in each government agency.